(untitled) (Revista Iberoamericana de Bioética, 2019)
The food industry, through advertising, has intensified the spread of obesogenic foods, a reality that may be a risk factor for the violation of children’s Human Right to Adequate Food (HRAF). In order to verify the influence of these advertisements in the violation of this right, from a bioethical perspective, Brazilian television channels were recorded, to subsequently analyze the nutritional composition of the food conveyed. Most of the foods found were of low nutritional quality, indicating interference in the guarantee of HRAF. Dialogue based on aspects such as human dignity, vulnerability, responsibility and the role of the State is necessary and should be used to promote the discussion of the theme and the development of policies that can guarantee the right to health.